Mistargeting of peroxisomal L-alanine:glyoxylate aminotransferase to mitochondria in primary hyperoxaluria patients depends upon activation of a cryptic mitochondrial targeting sequence by a point mutation. - Purdue, P E (1991)
In approximately one-third of primary hyperoxaluria type 1 patients, disease is associated with a unique protein sorting defect in which hepatic L-alanine:glyoxylate aminotransferase (AGT; EC 2.6.1.44), which is normally peroxisomal, is mistargeted to mitochondria. In all such patients analyzed to date, the gene encoding the aberrantly targeted AGT carries three point mutations, each of which specifies an amino acid substitution. In this paper we show that one of these substitutions, a proline-to-leucine at residue 11, is necessary and sufficient for the generation of a mitochondrial targeting sequence in the AGT protein. AGT with this substitution appears to interact specifically with the mitochondrial protein import machinery, via a discrete N-terminal domain of the AGT protein. The N-terminal 19 amino acids of AGT with this substitution are sufficient to direct mouse cytosolic dihydrofolate reductase to mitochondria, and a synthetic peptide corresponding to this same 19-amino acid region reversibly inhibits mitochondrial protein import, not only of AGT but also of ornithine transcarbamoylase, a genuine cytoplasmically synthesized mitochondrial protein. We have extended these studies to analyze a region of normal human AGT cDNA directly upstream of the coding region. This sequence appears to correspond to an ancestral mitochondrial targeting sequence deleted from the human coding region by point mutation at the initiation codon. We show that reestablishment of this initiation codon produces an active mitochondrial targeting sequence that is different to that found in the hyperoxaluria patients. These results are discussed with reference to the AGT targeting defect in primary hyperoxaluria and also in relation to the highly unusual species specificity of subcellular distribution of AGT among mammals.